2012
DOI: 10.5812/ijem.5305
|View full text |Cite
|
Sign up to set email alerts
|

ABCG8 Gene Responses to 8 Weeks Treadmill Running With or Without Pistachia atlantica (Baneh) Extraction in Female Rats

Abstract: BackgroundIt is well established that the excess cellular cholesterol concentration, as well as high density lipoprotein (HDL) and total cholesterol levels are strongly correlated with the incidence of coronary artery disease (CAD). Reverse cholesterol transport (RCT) is a term used to describe the efflux of excess cellular cholesterol. ABCG8 is a member of ABCG family that play a critical role in this process.ObjectivesThe current study was conducted to investigate the effect of endurance exercise with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
2
10
0
1
Order By: Relevance
“…Our results confirmed the previous findings and indicated that ABCG4 was also expressed in rat liver, kidney and visceral fat tissues, and the ABCG4 expression levels were lower in both control and trained Baneh treated tissues compared to their counterpart tissues treated by saline. Our GC-MS data analysis suggested that a lower ABCG4 expression in Baneh-treated tissues might be attributed to a higher content of unsaturated fatty acids, particularly elaidic acid in Baneh extract, which were partially in agreement with the previous reports [20,22,37,48]. de Vogel-dan den Bouch et al .…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirmed the previous findings and indicated that ABCG4 was also expressed in rat liver, kidney and visceral fat tissues, and the ABCG4 expression levels were lower in both control and trained Baneh treated tissues compared to their counterpart tissues treated by saline. Our GC-MS data analysis suggested that a lower ABCG4 expression in Baneh-treated tissues might be attributed to a higher content of unsaturated fatty acids, particularly elaidic acid in Baneh extract, which were partially in agreement with the previous reports [20,22,37,48]. de Vogel-dan den Bouch et al .…”
Section: Discussionsupporting
confidence: 92%
“…We found a lower and significant increase plasma HDL-C in saline trained rats and alower HDL-C concentrations in Bane-treated rats. Our data are consistent with previously reported results elsewhere [9,[48][49][50]82] …”
Section: Figure 8 Plasma Estradiol Level In Different Groupssupporting
confidence: 83%
“…In relation to the ghrelin response to herbal plants most of research fouced on the effects of Rikkunshito is an herbal medicine (in Japanes traditional medicine) on ghrelin secretion in human and animal subjects [41][42][43][44] Anacardiaceae family has been reported to be rich in essential fatty acids and antioxidants being found in nuts and it has also been measured that total amount of essential oils obtained from Pistachio-atlantica was higher than that from any other Pistachio species [45][46][47]. The effects of an aqueous extraction of pistachia-atlantica on HDL transporter factors such as ABCG8 and ABCG4 in female rats small intestine and kidney and also its effect on small intestine nesfatin-1 and visfatin with or without exercise have been reported elsewhere [40,[48][49][50]. With consider to the somewhat controversial reports and also the potential of ghrelin and Nesfatin-1 responses to any positive /negative change in energy balance, high-fat diet, and nutrients ,the present study was …”
Section: Aerobic Exercise and Herb Supplementation Increase Liver Andmentioning
confidence: 99%
“…In regard to exercise training, there is inconsistency in previous reports on the expression of cholesterol transporters at the intestinal apical side. Some authors reported an increase in intestinal ABCG8 gene and protein expression in treadmill-trained female rats compared to female Sed rats (Ghanbari-Niaki et al 2012). On the other hand, reduced ABCG8 gene expression was observed in the ileum of exercise-trained female rats compared to Sed female rat (Ngo Sock et al 2014b) probably due to a reduced need to efflux cholesterol back to the lumen as a consequence of lower cholesterol absorption (Wilund et al 2008).…”
Section: Discussionmentioning
confidence: 99%